Assuring Energy Reporting Integrity: Government Policy’s Past, Present, and Future Roles - Al-Madani, Mohammed Hammam Mohammed; Fernando, Yudi; Tseng, Ming-Lang (MDPI, 2022)
This study investigates government policy influence on energy reporting integrity in the past, present, and future. The study attempts to identify the dominating key themes in energy reporting and explore the function of government incentives and policies in influencing the integrity of energy consumption reports. A thorough literature review screening and theme identification were conducted through a systematic review. The data used in this study are mainly derived from English-language journals acquired from reputable academic databases such as Web of Science and Scopus. Social network analysis was used to examine the data retrieved with the VOSviewer software. The findings demonstrate that the key themes of government policy, energy reporting, energy management, and integrity are strongly focused in studies on energy policy, climate change, energy efficiency, renewable energy, life cycle assessment, carbon emissions, and sustainability. These topics included energy management, renewable energy, energy efficiency, emissions reporting, and energy transitions. The results suggest that there is little empirical support for how government policy promotes and validates the accuracy and integrity of energy reporting. The findings offer potential strategies for removing energy policy development, implementation, and reporting barriers. This study found that transparent disclosure of a company’s energy consumption attracts new investment. The integrity and transparency of the energy report attest to a firm’s commitment to working toward sustainable development goals. The study recommends that the government should align energy policies with clear guidelines about transparent energy disclosure and reform the existing sanctions and incentives to enforce the law.